2002
DOI: 10.1038/sj.ijo.0801998
|View full text |Cite
|
Sign up to set email alerts
|

Upper abdominal obesity, insulin resistance and breast cancer risk

Abstract: Overall adiposity in women adversely affects breast cancer risk mainly by greater exposure of mammary epithelial tissue to endogenous oestrogen. Upper abdominal adiposity appears to involve an additional effect related to the presence of insulin resistance. Aetiological factors in the development of hyperinsulinaemic insulin resistance are still uncertain but may involve aberrant susceptibility genes in adipocyte insulin receptors or in the insulin receptor substrate 1 pathway. Epigenetic factors are also like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 82 publications
1
47
1
5
Order By: Relevance
“…58 Aberrant insulin signaling, which leads to insulin resistance, hyperinsulinaemia and increased concentrations of endogenous estrogen and androgen, was linked to high breast cancer risk by clinical and experimental evidence. 59 The above mentioned functions confirmed the expression behavior of selected genes, in tumor samples of our study and in metanalysis results. A quite different situation was observed for the remaining upregulated gene, SLPI.…”
Section: Discussionsupporting
confidence: 61%
“…58 Aberrant insulin signaling, which leads to insulin resistance, hyperinsulinaemia and increased concentrations of endogenous estrogen and androgen, was linked to high breast cancer risk by clinical and experimental evidence. 59 The above mentioned functions confirmed the expression behavior of selected genes, in tumor samples of our study and in metanalysis results. A quite different situation was observed for the remaining upregulated gene, SLPI.…”
Section: Discussionsupporting
confidence: 61%
“…The factor(s) can be adsorbed by charcoal, because charcoal fully eliminated the growth-promoting effect of the ACCM. It is known that adipocytes are able to produce estrogen, which promotes breast cancer cell growth (20,35). However, estrogen cannot account for the SMC growth-promoting effect because estrogen does not stimulate but inhibits SMC proliferation as shown by our previous study (7).…”
Section: Discussionmentioning
confidence: 97%
“…The apparent differences in the association between adiponectin levels and breast cancer risk in pre-and postmenopausal periods need to be studied further. Indeed, previous epidemiological studies have shown an association of obesity and insulin resistance mainly with postmenopausal breast cancer (Stoll 2002, Michels et al 2003. Finding a significant inverse relationship between adiponectin and breast cancer risk among postmenopausal women in this and previous studies (Mantzoros et al 2004, Tworoger et al 2007 provides further support for the importance of adiponectin in the pathogenesis of malignancies associated with obesity-induced insulin resistance and hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%